TEACHING ENGLISH IN ENGLISH FOR SPECIFIC PURPOSES CONTEXT: CHALLENGES IN ENGLISH FOR BUSINESS MANAGEMENT - Retno Wiastuti; Ruminda Ruminda; Juhana Juhana (IKIP Siliwangi, 2024)
Understanding the principles and methods of Islamic finance and company management is crucial in today's global economy. Sharia Business Management, rooted in Islamic ethics, requires strong English proficiency for effective communication. Addressing the unique ESP challenges faced by students can enhance their professional success and improve education quality at UIN Raden Mas Said Surakarta. This finding depicts teaching challenges in English for Business Management. Through interviews and observations conducted at UIN Raden Mas Said Surakarta, specific difficulties faced by both teachers and students were identified. The primary finding of the research highlights several key challenges in learning and teaching ESP within the Sharia Business Management program. Students struggle with language proficiency, particularly with specialized vocabulary and complex ideas related to Sharia-compliant business practices, which hinders their academic and professional development. The research also identifies the need for contextualized English materials and improved course duration and facilities to enhance ESP education. Both lecturers and students recognize the significance of ESP for professional success in a globalized Sharia business environment, emphasizing the importance of mastering Islamic finance principles, legal terminology, cross-cultural communication, and specialized business documentation in English.